Media analysis techniques - Berger, Arthur Asa (Sage, 2019)
In the Sixth Edition of Media Analysis Techniques, author Arthur Asa Berger once again provides students with a clearly written, user-friendly, hands-on guide to media criticism. The book empowers readers to make their own analyses of the media rather than just accept how others interpret the media. Media Analysis Techniques begins by examining four basic techniques of media interpretation-semiotic theory, Marxist theory, psychoanalytic theory, and sociological theory-that Berger considers critical for creative people to acknowledge if they are to understand how their creations translate to the real world. Application chapters then link popular culture to these four theories. Written in an accessible style that demystifies complex concepts, Media Analysis Techniques includes learning exercises, a glossary, study guides, and the author's own illustrations.